UV dose investigation for imersed lamp purifier for electronic ballast UV lamps design - De Oro, Luis A. [UNESP]; Melo, Guilherme De A. [UNESP]; Canesin, Carlos A. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2014)
This paper presents a methodology of an electronic ballasts design for UV lamps filtering system, providing adjustable UV dose in order to ensure the inactivation of microorganisms' reproduction that are harmful to human health and can be present in drinking water. The project methodology is based on a so called MSSS model, used for defining the ultraviolet radiation applied to penstock purifiers, using immersed lamps on a water slide enclosure, which in combination with the hydraulic behavior, provide a good perspective of the microorganisms UV absorption along the entire purifier ducts structure. In addition, a water purifier was designed using CAD model, where hydrostatic simulations were applied to ensure compliance with the NSF/ANSI Standard 55, which provides drinking water directions for commercial and residential environments.
Keywords: MSSS model; UV dose; UV lamp; UV radiation